Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau - Febri Yuliani, Irmi Syakip Arsalan, Meyzi Heriyanto, (Jurnal Ilmu Administrasi Negara, 2020)
The Role of DPRD in Planning for Community Participation (Study of Community Participation in Development Planning Deliberations in Bengkalis District in 2018). This research is motivated by the realization of institutional participation represented by the Regional People’s Representatives Council in the administration of the government. This is as mandated in Law Number 23 of 2014 concerning Regional Government which states that DPRDs and Regional Heads are domiciled as administering elements of regional governments that are given the people’s mandate to carry out government affairs that are delegated to the regions. The purpose of this study was to determine the role of the DPRD in community participation planning in the Development Planning Connference in Bengkalis District in 2018. Data collection techniques in this study used interviews and observation. The analysis used in this study is a qualitative descriptive analysis consisting of data reduction (data reduction), data display (data presentation) and verification (describe conclusions).